ZnO Nanoparticle Transition Metal Doping: Effects on Charge Dynamics, Morphological and Magnetic Properties - Ravi, P.K.; Rajesh, P.; Kayashrini, S.; Abirami, S. Bala; Hisam, R. Mohamed (Asian Journal of Chemistry, 2026)
ZnO nanoparticles have attracted considerable interest owing to their structural stability, wide band gap, high exciton binding energy and diverse functional characteristics. Their practical performance, particularly in photocatalytic applications, is constrained by rapid electron–hole recombination and limited absorption in the visible region. In the present study, the pristine ZnO (Z1), Cu-doped ZnO (Z2) and Co-doped ZnO (Z3) nanoparticles were synthesized through a controlled co-precipitation route. The prepared materials were characterized by X-ray diffraction (XRD), UV-visible diffuse reflectance spectroscopy (UV-Vis DRS), photoluminescence (PL), Fourier-transform infrared spectroscopy (FT-IR), scanning electron microscopy (SEM), photocatalytic dye degradation and vibrating sample magnetometry (VSM). XRD analysis confirmed the retention of the hexagonal wurtzite ZnO phase after Cu and Co incorporation, accompanied by changes in crystallite characteristics and lattice parameters associated with dopant-induced strain and defect formation. SEM analysis indicated modifications in particle morphology, surface texture and aggregation behaviour upon metal-ion incorporation. The optical characteristics were strongly influenced by doping, with a shift in light absorption toward the visible region and a reduction in charge-carrier recombination, with the Co-doped sample (Z3) exhibiting the most pronounced response. The photocatalytic activity was influenced by the dopant-induced electronic states, which facilitated the separation of photogenerated electron–hole pairs and improved their participation in the photocatalytic process. VSM measurements further established changes in the magnetic response following transition-metal incorporation. The findings establish Cu and Co doping as effective approaches for tailoring the structural, optical, morphological and magnetic characteristics of ZnO nanoparticles, with Co incorporation providing a particularly notable modification of the investigated properties.